Modeling the decay of Escherichia Coli in different soils - Ling, Teck Yee; Kasing, A.; Rudy, H. J. (25th Malaysian Microbiology Symposium and 5th UNESCO National Workshop for the Promotion of Microbiology in Malaysia, 2014)
Bacteria originating from animal waste are known to contaminate soils and rivers. To better manage animal waste and protect water resources, the survival of fecal bacteria in different soils has to be studied and subsequently models can be developed to estimate the density of fecal bacteria on land at any time after disposal. Even though study of fecal bacteria decay has been conducted in soils of temperate origin, little is known about the behaviour of fecal bacteria in tropical soils. In this study, the decay rate of Excherichia coli (E. coli) in three different tropical soils from Sarawak, namely, peat soil, clay loam, and silt loam, was examined in the laboratory under constant temperature and saturated condition for a duration of 14 days. Results of this study indicated that the mean decay rate of E.coli ranged from 0.02d-1 on the clay loam to 0.14d-1 in the peat soil. The low decay rate in clay loam could be due to the higher quantity of clay particles in clay loam soil when compared to silt loam. This study also showed that E.coli population remained stable for 3 days in peat soil, 6 days in silt loam and as long as 10 days in clay loam. Even though peat soil has higher organic matter, the decay rate was higher than that of clay loam. This is possibly due to the high acidity of the peat soil. This study indicated that the modified version of the linear first-order decay model which accounted for lag period is an appropriate model in the prediction of E.coli decay in all the three soils for the duration studied. Furthermore, there is an indication that the potential of E.coli pollution in tropical countries is higher than in temperate countries due to the higher survival rate. Therefore, proper management practice in the application and the disposal of animal waste should be formulated and implemented.